Hypericin and Pheophorbide a Mediated Photodynamic Therapy Fighting MRSA Wound Infections: A Translational Study from In Vitro to In Vivo - Ben Chung Lap Chan; Priyanga Dharmaratne; Baiyan Wang; Kit Man Lau; Ching Ching Lee; David Wing Shing Cheung; Judy Yuet Wa Chan; Grace Gar Lee Yue; Clara Bik San Lau; Chun Kwok Wong; Kwok Pui Fung; Margaret Ip (MDPI AG, 2021)
High prevalence rates of methicillin-resistant Staphylococcus aureus (MRSA) and lack of effective antibacterial treatments urge discovery of alternative therapeutic modalities. The advent of antibacterial photodynamic therapy (aPDT) is a promising alternative, composing rapid, nonselective cell destruction without generating resistance. We used a panel of clinically relevant MRSA to evaluate hypericin (Hy) and pheophobide a (Pa)-mediated PDT with clinically approved methylene blue (MB). We translated the promising in vitro anti-MRSA activity of selected compounds to a full-thick MRSA wound infection model in mice (in vivo) and the interaction of aPDT innate immune system (cytotoxicity towards neutrophils). Hy-PDT consistently displayed lower minimum bactericidal concentration (MBC) values (0.625-10 µM) against ATCC RN4220/pUL5054 and a whole panel of community-associated (CA)-MRSA compared to Pa or MB. Interestingly, Pa-PDT and Hy-PDT topical application demonstrated encouraging in vivo anti-MRSA activity (>1 log10 CFU reduction). Furthermore, histological analysis showed wound healing via re-epithelization was best in the Hy-PDT group. Importantly, the dark toxicity of Hy was significantly lower (p < 0.05) on neutrophils compared to Pa or MB. Overall, Hy-mediated PDT is a promising alternative to treat MRSA wound infections, and further rigorous mechanistic studies are warranted.